Efectos del estrés laboral en los profesionales de enfermería del Hospital General Francisco de Orellana. Año 2013 -2014 - Cargua Quishpe, July Roxana (2015)
This research is entitled "Effects of work stress in Nursing Professionals Francisco of Orellana of General Hospital. Year 2013 -2014” was guided at identifying the effects of work stress in the professionals. The research was type: cross fixed, it is descriptive and bibliographical. He appealed to the survey as a research technique and as instrument was used two questionnaires were applied to 25 nurses, among the most relevant results of the study of 25 nurses it observed that in full are personal respondent they are women most of whom said they had experienced job stress at an low level represented by 60% of the total, with the main causes with 80% respectively job insecurity and work overload, manifested by job strain with 60% and physical exhaustion with 56% of the total surveyed. It was determined that the nurse is highly susceptible to develop stress from work pressures that do not conform to their knowledge and skills, and test their ability to cope with a situation. It was developed as a proposed intervention motivational talk based on the recommendations applicable practices as relaxation and breathing exercises to prevent or reduce work stress with the aim of improving the quality of life of staff and nursing care. Keywords: Job Stress, Professional Nursing